Democracies, Populisms, and the State in Latin America. Some observations for the current debate - Puhle, Hans-Jürgen (Revista del CLAD Reforma y Democracia, 2025)
The brief observations focus on some key challenges that Latin American states are currently confronting, and on the question of how they can function effectively in their present state and under the pressures of polarizing transformations. There will be four points: First, the current state of democracies will be discussed, which is basically characterized by processes of democratic erosion or recession. Second, the challenges posed by the various populist movements, politics, and regimes will be addressed, which have proliferated and changed, making them more radical, aggressive, and detrimental to democratic politics. The third section will be dedicated to the problems of the functioning of the states in Latin America, their aspirations, shortcomings, and deviations, and the transformations the model of the weak ‘strong developmental state’ has gone through during the last half-century. In the final fourth point, some recommendations for political action and for further clarification and research will be debated (‘what could be done’).